2020
DOI: 10.1080/13880209.2019.1711430
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Moist Exposed Burn Therapy and Ointment (MEBT/MEBO) on the autophagy mTOR signalling pathway in diabetic ulcer wounds

Abstract: Context: Burn therapy (MEBT)/moist exposed burn ointment (MEBO) is an effective traditional Chinese medicine method to treat diabetic wound, but the mechanism is unclear. Autophagy has been proved to be closely related with wound healing, so MEBO/MEBT is hypothesized to promote diabetic wound healing by regulating autophagy. Objective: To explore the mechanism of moist exposed MEBT/MEBO promoting diabetic wound repair. Materials and methods: Eighty male Wistar rats were randomly assigned to control (n ¼ 20) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Many studies reported the mechanism of MEBO, it could improved the microcirculation of the tissue, participate in neurovascularization of the wound and epithelial regeneration. The earlier clinical usage is for local the treatment of burn injury and ulcer including diabetic ulcer [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies reported the mechanism of MEBO, it could improved the microcirculation of the tissue, participate in neurovascularization of the wound and epithelial regeneration. The earlier clinical usage is for local the treatment of burn injury and ulcer including diabetic ulcer [4].…”
Section: Discussionmentioning
confidence: 99%
“…One theory proposed to explain capecitabine-associated HFS is that specialized skin cells (keratinocytes) might have upgraded levels of the enzyme thymidine phosphorylase. Another theory suggests that capecitabine may be eliminated by the eccrine system (sweat secretion), and HFS is caused by an unknown mechanism related to the increased number of eccrine glands present in the hands and feet [3], [4], [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that autophagy is involved in the regulation of a number of cellular functions and is closely related to the development of diseases, such as cancer, aging, and trauma, and is currently a hotspot in research (6,7). Autophagy can reduce the production of inflammatory factors, induce wound angiogenesis, reepithelialization and scar formation in the process of wound healing, and can also improve the impaired cell activity in high glucose environment (8)(9)(10)(11). However, the mechanism of the role of autophagy in trauma healing is still unclear.…”
Section: Original Articlementioning
confidence: 99%
“…Moistened exposure burn therapy (MEBT) is a local treatment method that treats burn wounds with moist exposed burn ointment(MEBO) and exposes burn tissue to repair and regeneration in a physiologically moist environment. MEBO applied to the wound surface can effectively improve the microcirculation in the zone of stasis and prevent the progressive necrosis of the tissue nearby (41). The advantages of MEBT are as follows: First, MEBT can effectively improve the microcirculation of the wound, avoiding the formation of a large number of microthrombosis and reducing the degree of ischemia and hypoxia in the zone of stasis.…”
Section: Moistened Exposure Burn Therapy (Mebt)mentioning
confidence: 99%